Análisis de los principios tributarios de: simplicidad, legalidad, generalidad, proporcionalidad y eficacia en la evolución del formulario del impuesto a la renta y los impactos para su aplicación para sociedades y personas naturales - Piñarcaja Toapanta, Christian Javier (2014)
Taxes are certainly an important source of income in a country, and depends on the legal and administrative organization that given to the agency responsible for tax collection and administration, for it to make a smooth and adequate management. In Ecuador, the Internal Revenue Service, which is responsible for the Tax Administration has shown a fairly adequate with increasing levels of effectiveness in carrying out their work, and in recent years has proposed nine amendments to the tax legislation, with the which has significantly increased values for taxes in the country. Not only the processes but also the forms for the declaration of income tax required permanent improvement reviews that couples simplicity tax principles, legality, generality, proportionality and effectiveness, for better understanding, calculation and reporting especially easily and payment of the obligation.